2016
DOI: 10.1039/c5nj02809d
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous MEL, BEA, and FAU zeolite crystals obtained by in situ formation of carbon template over metal nanoparticles

Abstract: Here, we report the synthesis and characterization of hierarchical zeolite materials with MEL, BEA and FAU structures. The synthesis is based on the carbon templating method with an in-situ-generated carbon template. Through the decomposition of methane and deposition of coke over nickel nanoparticles supported on silica, a carbon-silica composite is obtained and exploited as a combined carbon template/silica source for the zeolite synthesis. The mesoporous zeolite materials were all prepared by hydrothermal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Indeed, there are many types of catalysts that have been used for the conversion of glucose to HMF, such as metal chloride salts (MgCl 2 , SnCl 4 ) [7], metal oxides (TiO 2 , ZrO 2 , Nb 2 O 5 ) [8,9], metal organic frameworks (ZIF-8) [10], zeolites [11][12][13][14][15][16], and Sn, Ti and Zr-containing zeolites [17,18]. Among them, the metal incorporated in a zeolite is one of the most important candidates for this reaction because of high metal dispersion [19], high surface area [20], unique shape selective properties [21], suitable acid properties [22] and high thermal/hydrothermal stability [23], for example.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there are many types of catalysts that have been used for the conversion of glucose to HMF, such as metal chloride salts (MgCl 2 , SnCl 4 ) [7], metal oxides (TiO 2 , ZrO 2 , Nb 2 O 5 ) [8,9], metal organic frameworks (ZIF-8) [10], zeolites [11][12][13][14][15][16], and Sn, Ti and Zr-containing zeolites [17,18]. Among them, the metal incorporated in a zeolite is one of the most important candidates for this reaction because of high metal dispersion [19], high surface area [20], unique shape selective properties [21], suitable acid properties [22] and high thermal/hydrothermal stability [23], for example.…”
Section: Introductionmentioning
confidence: 99%
“…A hierarchical pore system facilitates mass transport while maintaining the zeolite shape selectivity [37]. Abildstrøm et al [38] indicated that the introduction of an even moderate degree of mesoporosity during the synthesis could improve the ability for the ion exchange of zeolite Y and thus lead to an improved and more stable ion exchange process at industrial scale.…”
Section: Resultsmentioning
confidence: 99%
“…X‐ray powder diffraction patterns were obtained for the three materials which is shown in Figure . The diffraction patterns of the three materials (Figure top) are consistent with a FAU structure for Pt@H−Y and a CHA structure for both Pt@K‐CHA and Pt/K−CHA ,. To evaluate the size of the Pt particles Figure bottom shows a zoomed part of the diffraction pattern.…”
Section: Resultsmentioning
confidence: 99%